2005
DOI: 10.1016/j.bmcl.2004.11.072
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Diazepane-2,5-diones as novel inhibitors of LFA-1

Abstract: 1,4-Diazepane-2,5-diones (2) are found to be a new class of potent LFA-1 inhibitors. The synthesis, structure, and biological evaluation of these 1,4-diazepine-2,5-diones and related derivatives are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 42 publications
0
28
0
2
Order By: Relevance
“…Importantly, the anti-CD11a blocking antibody Efalizumab is currently approved for the treatment of psoriasis with several other novel small molecule CD11a antagonists currently under development. [64][65][66][67][68] Our findings together with previous reports of CD11a and CD18 expression in human IBD specimens suggest that targeting of these molecules may provide another therapeutic treatment for IBD.…”
Section: Discussionmentioning
confidence: 53%
“…Importantly, the anti-CD11a blocking antibody Efalizumab is currently approved for the treatment of psoriasis with several other novel small molecule CD11a antagonists currently under development. [64][65][66][67][68] Our findings together with previous reports of CD11a and CD18 expression in human IBD specimens suggest that targeting of these molecules may provide another therapeutic treatment for IBD.…”
Section: Discussionmentioning
confidence: 53%
“…has been co-crystalized with a number of small molecule inhibitors 131,[140][141][142][143][144][145] identifying the first model of true allosteric inhibition of an α-I domain (FIG. 5b).…”
Section: Role Of Integrin Cytoplasmic Tailsmentioning
confidence: 99%
“…Crystallographic studies have demonstrated that the small molecules bind to a pocket in contact with the α7 helix on the opposite side of the molecule from the MIDAS domain [140][141][142][143][144][145] . This region has been previously shown to be important for ligand binding and receptor function [146][147] .…”
Section: Role Of Integrin Cytoplasmic Tailsmentioning
confidence: 99%
“…Die Bindungsachse zwischen LFA-1 und ICAM-1 wurde aus diesem Grund bereits früher als mçglicher Ansatzpunkt für die Medikamententwicklung beschrieben. [4][5][6][7] Allerdings stellt die Konformationsänderung von niedrig affinen zu hochaffinen Zuständen, die mit der Bindung von LFA-1 an ICAM-1 einhergeht, eine erhebliche Hürde für die Konstruktion von LFA-1-Inhibitoren dar. [8,9] Obwohl die Inhibierung von Protein-Protein-Interaktionen (PPIs) mittels kleiner Moleküle lange Zeit als die ultimative Herausforderung in der Wirkstoffentwicklung galt, wurden nur sehr wenige Beispiele für solche PPI-Inhibitoren beschrieben.…”
unclassified
“…Auch konnte die durch 1 induzierte Affinitätssteigerung von LFA-1 zu ICAM-1 durch die Zugabe des bekannten LFA-1-Inhibitors AAQ552, der in die Mevinolin-Bindungstasche der I-Domäne bindet, komplett aufgehoben werden (Abbildung 3 B). [6] Zusätzlich zu dieser Fähigkeit, die Bindung von ICAM-1 an aktivierte T-Zellen auszulçsen, verstärkte 1 auch die Aggregation von T-Zellen, einen Prozess, der wiederum von der Interaktion zwischen LFA-1 und ICAM-1 abhängt (Abbildung 3 C). [26,27] Die dosisabhängige Induktion der TZellen-Aggregation konnte durch einen monoklonalen Antikçrper gegen LFA-1 vollständig blockiert werden (Abbildung 3 D).…”
unclassified